The crossover - Kwame, Alexander (New York: Houghton Mifflin Harcourt, 2014)
Fourteen-year-old twin basketball stars Josh and Jordan wrestle with highs and lows on and off the court as their father ignores his declining health.
Keywords: Novels in verse; Basketball -- Fiction; Twins -- Fiction; Brothers -- Fiction; Father and sons -- Fiction; African Americans -- Fiction